ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT IN RIAU PROVINCE - Enni Savitri; Andreas Andreas; Volta Diyanto; Tatang Ary Gumanti (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
Accountability refers to the activity of informing all parties who have the right to request information, or in other words, reporting on action to individuals, legal entities, or collective leaders of organizations. This study aims to analyze the effect of village officials’ competence, internal control system, community participation, and utilization of information technology on the accountability of village fund management. The population of this study include the village officials, totaling 416 people, consisting of the village head, village secretary, government section, welfare section, head of planning affairs, and head of general affairs in 104 villages in Pelalawan Regency, Riau Province. The study employs a non-probability sampling method and multiple linear regression to test the hypotheses. The results indicate that the village officials’ competence, internal control system, community participation, and utilization of information technology affect the accountability of village fund management.